Adhesive strips as the sole method for skin closure is effective in total knee arthroplasty - Varah Yuenyongviwat; Khanin Iamthanaporn; Pakjai Tuntarattanapong; Kantapon Dissaneewate; Preyanun Tangjatsakow; Wongthawat Liawrungrueang; Theerawit Hongnaparak (Journal of Orthopaedic Surgery, 2019)
Objective: Adhesive strips are used as the sole method for skin closure in many operations except total knee arthroplasty. The claims are decreased wound closure time, less tissue reaction, and lack of stitch marks. The purpose of this study was to compare the efficacy of closure using adhesive strips versus running subcuticular stitches. Methods: This study was a retrospective case-matched study. Running subcuticular stitches or adhesive strips were used for skin closure in 151 and 137 patients, respectively. All of the patients had an operation by a single surgeon and had the same patient care protocol. All of the patients were evaluated postoperatively for wound complication at 2 weeks, 6 weeks, and 3 months follow-up. Results: The wounds of most patients in both groups had healed. The incidence of superficial infection was not different between the groups (1.32% in the running subcuticular suture group and 1.46% in the adhesive strip group) ( p = 0.92). One case (0.66%) in the running subcuticular suture group had deep infection, which required reoperation ( p = 0.34). The patients in the running subcuticular suture group had higher unabsorbable sutures, which required further removal compared to the adhesive strip group ( p < 0.001). Conclusion: The use of adhesive strips is an effective skin closure method with a low rate of infection and skin complications. This technique is easy and there is no need for suture removal. Furthermore, there are no stitch marks and the cost of suturing is lower.